ФОРМУВАННЯ МИСТЕЦТВОЗНАВЧИХ ПОНЯТЬ ЯК УМОВА ПРОФЕСІЙНОЇ ПІДГОТОВКИ ВЧИТЕЛЯ МИСТЕЦЬКИХ ДИСЦИПЛІН (Педагогіка вищої та середньої школи, 2006)
In article the opportunity of interpretation of the contents of art criticism concepts is analyzed' their structural components are allocated, attempt to extrapolate components of modern information technologies in formation of art criticism concepts of the teacher of arts is made.